The Impact of Green Accounting and Environmental, Social, and Governance Disclosure on Corporate Value with Profitability as a Moderating Variable - Laela, Naili Vivi Nur; Widuri, Trisnia (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research investigates the impact of green accounting and environmental, social, and governance (ESG) factors on firm value, with profitability (ROA) serving as a moderating variable within basic material companies listed on the Indonesia Stock Exchange. This research employs a quantitative methodology featuring an associative approach, utilizing panel data from 15 companies over the period of 2022 to 2024, resulting in a total of 45 observations. The analysis of the panel data regression model involved the application of the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), leading to the conclusion that REM is the most suitable model. The findings indicate that green accounting and ESG do not exert a meaningful influence on firm value. Furthermore, ROA does not serve as a moderator in the relationship between green accounting and ESG concerning firm value. The results suggest that sustainability practices within Indonesia's mining and basic industry sectors remain largely symbolic, lacking significance for investors and failing to deliver robust market signals. This research highlights the importance of enhancing the quality of sustainability reporting, strengthening regulatory oversight, and advancing investor education to ensure that sustainability genuinely contributes value to organizations